(untitled) (Baltic Journal of Sport and Health Sciences, 2014)
Background. Research aim was to establish the influence of a prior anaerobic load on the kinetics of ventilation (V E ) and carbon dioxide output (VCO 2 ) during on- and off-transition phases of intermittent increasing cycling exercise. Methods. The seven healthy, physically active females volunteered to estimate the influence of a prior anaerobic load on the kinetics of respiratory parameters. During the first visit VO 2 max was evaluated using the increasing cycling exercise test. During the second testing the participants performed intermittent cycling exercise (ICE). During the other visit they performed supramaximal 30 s anaerobic exercise and after 15 min of the rest – ICE. In order to estimate the kinetics of respiratory parameters were analysed by adopting mono-exponential function. Results. Mean blood lactate concentration was increased during ICE performed after prior anaerobic load in the presence of a residual metabolic acidosis. The asymptote and amplitude of monoexponential function reflecting VCO 2 kinetics during on- and off-transitions were not changed after prior anaerobic load. The time constant of this function was significantly longer (p < .01) both during on- and off-transitions at work rate below lactate threshold (LT), whereas this parameter at higher work intensities remained unchanged. The parameters of V E monoexponential function during on- and off-transitions were not changed after prior anaerobic load. Conclusion. Despite similar physiological mechanism responsible for V E and CO 2 regulation during exercise the prior anaerobic load had different influence on the ventilation and VCO 2 kinetics during exercise below lactate threshold causing slowing of VCO 2 without changes of V E kinetics. Keywords: exercise intensity, lactate threshold, pulmonary ventilation, CO2 output, acidosis.